Impact of stray inductances of the power loop on false trigger‐on in the zero‐voltage‐switching full‐bridge converter. (28th June 2016) - Qian, Qinsong; Zhang, Taizhi; Sun, Weifeng; Lu, Shengli
Summary: Here, we propose an exhaustive theoretical investigation and experimental verification of the false trigger‐on phenomenon, which would lead to the interaction between the upper and lower devices during the switching transient, in the zero‐voltage‐switching (ZVS) full‐bridge converter. An equivalent model of the converter, which takes not only the parasitic capacitors of the metal–oxide–semiconductor field‐effect transistors into account but also the stray inductances of the main circuit, is presented. Based on the model, a comprehensive study of the false trigger‐on phenomenon is carried out. According to the analysis results, the stray inductances of the metal–oxide–semiconductor field‐effect transistors have negligible influence on the false trigger‐on phenomena since the soft‐switching is realized. The false trigger‐on phenomenon is induced by the stray inductances of the main circuit. Moreover, the arrangement of the switching sequence would cause significant discriminations in the false trigger‐on phenomena because of the specific working mode of the ZVS full‐bridge converter. According to the investigation results, optimization methods are presented to suppress the induced voltage. At last, the theoretical investigations are verified by tests of a ZVS full‐bridge converter. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper presents an exhaustive theoretical investigation and experimental verification on the false trigger‐on phenomena, which would lead to the interaction between the upper and lower devices during the switching transient, in the zero‐voltage‐switching (ZVS) full‐bridge converter. An equivalent model is proposed taking into account not only the parasitic capacitances of the metal–oxide–semiconductor field‐effect transistors but also the stray inductances of the main circuit.